(untitled) (Research, Society and Development, 2021)
Sexually Transmitted Diseases (STDs) have become increasingly frequent worldwide, so they have become a major public health problem. The study aimed to describe the feelings experienced by women regarding the diagnosis of HIV / AIDS in a Serological Reference Center. It was a qualitative, exploratory, descriptive and explanatory research. As for the main results, the discovery of the HIV / AIDS diagnosis was seen as a moment of transition in the person’s life. It disorganizes being, relationships and life in society, especially among those closest to us, such as family and friends. This moment is also accompanied by uncertainty, anxiety, insecurity, fear of an unknown and frightening situation. Therefore, in the confrontation with the new reality, the person experiences moments of suffering. It is concluded that women who live with the HIV virus faced divergent and conflicting situations when receiving the seropositive diagnosis to learn to live with this new reality.